Distance Education: An Investigation of Tutors’ Electronic Feedback Practices during Coronavirus Pandemic - AbuSa'aleek, Atef O.; Alotaibi, Abdullah N. (International Journal of Emerging Technologies in Learning (iJET), 2022)
The current study investigated the patterns of English language tutors’ e-feedback practices during the coronavirus pandemic, learners’ response to tutors’ e- feedback and the important issues that emerged from e-feedback practices. Quantitative and qualitative analysis of the online questionnaire and the semi-structured interviews were performed. The findings indicate that (1) English language tutors concentrate slightly more on local issues than global issues, provide eight main types of e-feedback; clarification requests, general explanations and clarification, questions and commands, repetition, explicit feedback, elicitation and recasts respectively. In addition, tutors employ more written and audio e-feedback compared with the screencast via various online platforms such as Blackboard collaborative tools, Zoom, Microsoft Teams, Email, and WhatsApp. (2) The findings indicate that the students ask for more clarifications, express their understanding of the e-feedback, engage in discussions, comprehend the e-feedback and make successful revisions, express their misunderstanding of the e-feedback and just a few students ignore the e-feedback they receive. (3) The qualitative analysis of the semi-structured interviews revealed some important issues such as the tutors' preferences to online learning, the appropriateness of online platform tools in providing e-feedback, ways and timing of providing e-feedback.